A Monte Carlo‐based dosimetric characterization of Esteya®, an electronic surface brachytherapy unit. Issue 1 (28th November 2018) - Valdes‐Cortez, Christian; Niatsetski, Yury; Perez‐Calatayud, Jose; Ballester, Facundo; Vijande, Javier
Abstract : Purpose: The purpose of this work is threefold: First, to obtain the phase space of an electronic brachytherapy (eBT) system designed for surface skin treatments. Second, to explore the use of some efficiency enhancing (EFEN) strategies in the determination of the phase space. Third, to use the phase space previously obtained to perform a dosimetric characterization of the Esteya eBT system. Methods: The Monte Carlo study of the 69.5 kVp x‐ray beam of the Esteya ® unit (Elekta Brachytherapy, Veenendaal, The Netherlands) was performed with PENELOPE2014. The EFEN strategies included the use of variance reduction techniques and mixed Class II simulations, where transport parameters were fine‐tuned. Four source models were studied varying the most relevant parameters characterizing the electron beam impinging the target: the energy spectrum (mono‐energetic or Gaussian shaped), and the electron distribution over the focal spot (uniform or Gaussian shaped). Phase spaces obtained were analyzed to detect differences in the calculated data due to the EFEN strategy or the source configuration. Depth dose curves and absorbed dose profiles were obtained for each source model and compared to experimental data previously published. Results: In our EFEN strategy, the interaction forcing variance reduction (VRIF) technique increases efficiency by a factor 20. Tailoring the transport parameters values (C1 and C2) does not increase the efficiency in a significant way. Applying a universal cutoff energy EABS of 10 keV saves 84% of CPU time while showing negligible impact on the calculated results. Disabling the electron transport by imposing an electron energy cutoff of 70 keV (except for the target) saves an extra 8% (losing in the process 1.2% of the photons). The Gaussian energy source (FWHM = 10%, centered at the nominal kVp, homogeneous electron distribution) shows characteristic K‐lines in its energy spectrum, not observed experimentally. The average photon energy using an ideal source (mono‐energetic, homogeneous electron distribution) was 36.19 ± 0.09 keV, in agreement with the published measured data of 36.2 ± 0.2 keV. The use of a Gaussian‐distributed electron source (mono‐energetic) increases the penumbra by 50%, which is closer to the measurement results. The maximum discrepancy of the calculated percent depth dose with the corresponding measured values is 4.5% (at the phantom surface, less than 2% beyond 1 mm depth) and 5% (for the 80% of the field) in the dose profile. Our results agree with the findings published by other authors and are consistent within the expected Type A and B uncertainties. Conclusions: Our results agree with the published measurement results within the reported uncertainties. The observed differences in PDD, dose profiles, and photon spectrum come from three main sources of uncertainty: intermachine variations, measurements, and Monte Carlo calculations. It has been observed that a mono‐energetic source with a Gaussian electron distribution over the focal spot is a suitable choice to reproduce the experimental data.